Efektivitas Daya Tarik Iklan dan Kualitas Produk terhadap Keputusan Pembelian Produk Bulog pada Perusahaan Umum Bulog Kantor Wilayah Kalimantan Selatan - Fatimah Fatimah; Novi Shintia; Muhammad Wahyu Wardhana (P3M Politeknik Negeri Banjarmasin, 2023)
The problem faced by the public company BULOG is the instability of sales turnover through the advertising promotion media carried out, so that sales turnover becomes unstable. This research was conducted with the aim of knowing the Effectiveness of Advertising Attractiveness and Product Quality on purchasing decisions for BULOG products which have so far been applied and will be applied to the BULOG Public Company South Kalimantan regional office. The research method used in this Final Project research is descriptive with qualitative data techniques, data collection from research is carried out by observation, interviews and documentation. The results of the study indicate that the promotion strategy through advertising media is still not optimal, resulting in unstable sales turnover. For this reason, companies must be able to maximize the attractiveness of advertising on product purchasing decisions by carrying out marketing activities through effective advertising media and using advertising media promotion strategies on Instagram Reels to solve problems.